Challenges on the path toward sustainability in Europe : social responsibility and circular economy perspectives - Redek, Tjaša (Bingley, U.K. : Emerald Publishing Limited, 2020)
Challenges On the Path Toward Sustainability in Europe provides readers with guidance on sustainable actions at firm, consumer and institutional level. It studies the wide ranging challenges of implementing the sustainable development goals in Europe, while also addressing the challenges for key stakeholders in the economy. Vesna Zabkar and Tjaša Redek offer a theoretical and empirical approach to addressing sustainable development, providing rich data analysis at cross-country level, as well as practical examples from the European context. Its scientific outlook is based on extensive theoretical and empirical data analysis, however refraining from an extensively technical approach. Challenges On the Path Toward Sustainability in Europe is of direct relevance to both academics and practitioners seeking to expand their practical knowledge the subject as well as a richer theoretical background for analysing this field at the intersection of environmental and resource economics.
Chapter 1: The challenges on the path towards sustainability in the EU / Vesna Zabkar, Tjaša Redek -- Part 1: Where does Europe stand? -- Chapter 2: Sustainable development goals in the EU and the challenges in their implementation / Tjaša Redek, Polona Domadenik, Matjaž Koman -- Chapter 3: How far is the European Union from sustainable development goals / Matjaz Koman, Polona Domadenik, Tjaša Redek -- Part 2: The corporate and consumer perspective -- Chapter 4: Strategic CSR: mapping the state-of-the-art / Barbara Čater, Urša Golob, Vesna Zabkar -- Chapter 5: Towards better understanding of the corporate sustainability concept / Tomaž Čater, Patricia Fux -- Chapter 6: Why does a firm go bankrupt? / Denis Marinšek -- Chapter 7: Innovation for a greener and more profitable future: a conceptual approach / Polona Domadenik, Matjaž Koman, Francesco Pastore -- Chapter 8: Environmental-sustainability aspect in the outsourcing of business-logistics services / Marko Jakšič, Marko Budler -- Chapter 9: Sustainable market exchange from the consumer perspective / Barbara Culiberg, Mateja Kos Koklic, Vesna Zabkar, Katarina K. Mihelič -- Part 3: The socio-economic and regulatory context of sustainable development -- Chapter 10: National transfer accounts indicators of economic dependency in the EU countries / Jože Sambt, Tanja Istenič -- Chapter 11: Promoting well-being through intergenerational transfers and gender equality in 25 EU countries / Tanja Istenič, Jože Sambt, Daša Farčnik -- Chapter 12: The importance of human capital for sustainability / Daša Farčnik, Tanja Istenič -- Chapter 13: Reinforcement of social sustainability through education and public intangible capital / Eva Erjavec -- Chapter 14: Over-regulation, degradation of the rule of law and implementation of sustainable practices / Mitja Kovac, Ann-Sophie Vandenberghe -- Chapter 15: Towards a sustainable future: challenges ahead / Aleksandar Kecšeljević, Tjaša Redek, Vesna Zabkar.
Includes index.
Print version record.
Keywords: Sustainable development -- Europe; Social responsibility of business -- Europe; Sustainability -- Europe; Business & Economics -- Economic Conditions; Economic systems & structures